2016
DOI: 10.15761/cogrm.1000138
|View full text |Cite
|
Sign up to set email alerts
|

Long-term health effects in children exposed in utero to hyperemesis gravidarum

Abstract: Objective: Previously we reported on the increased risk of adverse neurodevelopmental outcomes in children exposed in utero to hyperemesis gravidarum. The purpose of this study is to determine the frequency of non-neurodevelopmental long-term health effects in children exposed in utero to hyperemesis gravidarum and to identify prognostic factors for these disorders. Study design:Long-term outcomes of 312 children from 203 mothers with hyperemesis gravidarum were compared to outcomes from 169 children from 89 u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Although causality cannot be proven based on this observational study, there is strong biological plausibility based on the effect of maternal malnutrition on the developing brain at critical time points (31,32) . A study of 312 children exposed in utero to HG found they have a 3•82fold increase of being diagnosed with conditions including allergies, chronic constipation, growth restriction and chronic respiratory infections (33) . The authors postulate that failure to gain enough weight during pregnancy puts the child at risk for intra-uterine growth restriction, which in turn could incur greater risk for other neurodevelopmental and physical problems.…”
Section: Effects Of Hg On Offspringmentioning
confidence: 99%
“…Although causality cannot be proven based on this observational study, there is strong biological plausibility based on the effect of maternal malnutrition on the developing brain at critical time points (31,32) . A study of 312 children exposed in utero to HG found they have a 3•82fold increase of being diagnosed with conditions including allergies, chronic constipation, growth restriction and chronic respiratory infections (33) . The authors postulate that failure to gain enough weight during pregnancy puts the child at risk for intra-uterine growth restriction, which in turn could incur greater risk for other neurodevelopmental and physical problems.…”
Section: Effects Of Hg On Offspringmentioning
confidence: 99%
“…One condition likely to cause nutritional deficiency is Hyperemesis gravidarum (HG). HG is defined by weight loss through excessive vomiting during pregnancy and plays a significant role in health outcomes [9,10]. These effects are long term, in that in utero exposure to HG is significantly associated with poor postnatal mental health outcomes for the child [10].…”
Section: Nutritional Stress and Pregnancy Outcomesmentioning
confidence: 99%